2020
DOI: 10.24191/idealogy.v5i2.228
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Malaysian and Japanese Textile Motifs Through Product Diversification: Home Décor

Abstract: Malaysian textile motifs especially the Batik motifs and its product are highly potential to sustain in a global market. The integration of intercultural design of Malaysian textile motifs and Japanese textile motifs will further facilitate both textile industries to be sustained and demanded globally. Besides, Malaysian and Japanese textile motifs can be creatively design on other platforms not limited to the clothes. Therefore, this study is carried out with the aim of integrating the Malaysian textile motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Malaysian batik motifs eventually progressed predominantly into floral and geometric stylization as dictated by Islamic doctrine (Salleh, 2019; Yunus, 2011). A prominent batik motif that is continuously used until today is known as pucuk rebung which was inspired by the tapered triangular feature of rebung or bamboo shoot (Arney, 1987; Legino, 2016; Samsuddin et al, 2020) as shown in Figure 2. Legino et al’s (2015) study on various motifs of Malaysian batik sarong and proposed that there were two delineated shifts in design that were brought upon by the constitutional and policy changes in Malaysia.…”
Section: Batik Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malaysian batik motifs eventually progressed predominantly into floral and geometric stylization as dictated by Islamic doctrine (Salleh, 2019; Yunus, 2011). A prominent batik motif that is continuously used until today is known as pucuk rebung which was inspired by the tapered triangular feature of rebung or bamboo shoot (Arney, 1987; Legino, 2016; Samsuddin et al, 2020) as shown in Figure 2. Legino et al’s (2015) study on various motifs of Malaysian batik sarong and proposed that there were two delineated shifts in design that were brought upon by the constitutional and policy changes in Malaysia.…”
Section: Batik Productionmentioning
confidence: 99%
“…(A) Triangular outline of pucuk rebung or bamboo shoot (source: Legino, 2016). (B) Pucuk rebung stylization in batik stamp sarong (source: Samsuddin et al, 2020). (C) Modern stylization of Pucuk rebung in pastel colors.…”
Section: Batik Productionmentioning
confidence: 99%
See 1 more Smart Citation